Una storiografia meticcia. Note sull’opera di Serge Gruzinski. (Altre Modernità, 2009)
This paper aims to acquaint the reader with the works of Serge Gruzinski. Historian, professor at the École des Hautes Études en Sciences Sociales (Paris), since the 1980s Gruzinski has put the phenomenon of globalization into an historical perspective. From La colonisation de l'imaginaire (1988) up to Quelle heure est-il là bas? (2008), through Les Quatre parties du monde (2004) and the exhibition La planète métisse (Paris, Musée du Quai Branly, 2008-2009), Gruzinski has developed his scientific task from a very original point of view. With a special focus on Mexico and the Spanish-American experience, he has in fact followed the hints of globalization in the long period of history of civilizations, cultures, peoples and individuals. His works cross many frontiers. By connecting different spaces and times, different sources and scholarly traditions, the researches analyzed in this paper expose the reader to the whole gamut of cultural experiences fostered by globalization. In Gruzinski's perspective, history, far from being an ancilla of social sciences, remains the fundamental tool to understand and cope with the huge political and cultural changes of contemporary international life whose origins are rooted in the early modern age (XV-XVI century).
Keywords: Globalizzazione; Gruzinski Serge; Mondializzazione; Métissage/Meticciato; Occidentalizzazione; Storia moderna